2020
DOI: 10.1016/j.heliyon.2020.e03439
|View full text |Cite
|
Sign up to set email alerts
|

The trustworthiness of travel and tourism information sources of social media: perspectives of international tourists visiting Ethiopia

Abstract: Credibility of social media travel information sources is one of the most debatable topics among scholars. This research is designed to address the trustworthiness of travel and tourism information sources of social media platforms. Cross-sectional research design and convenience sampling was applied. Statistical Package for Social Science version 23 was employed to compute mean, one sample T-test, independent sample T-test and one-way Analysis of variance. Eta squared was calculated to measure the effect size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 43 publications
2
55
0
3
Order By: Relevance
“…However, the researcher found that there was still a lack of access to information about North Sulawesi tourism, especially on social media. This finding is in line with research conducted at the Department of Tourism and Culture of the City of Manado (Berhanu & Raj, 2020) which found that the use of communication media in tourism promotion activities did not make tourism promotion run well. This was caused by, among others, the lack of funds to finance operations, problematic network systems, there were lack of IT and design expert permanent employees in the organisational structure, as well as inadequate office facilities and infrastructure.…”
Section: Regional Tourism Brandingsupporting
confidence: 86%
“…However, the researcher found that there was still a lack of access to information about North Sulawesi tourism, especially on social media. This finding is in line with research conducted at the Department of Tourism and Culture of the City of Manado (Berhanu & Raj, 2020) which found that the use of communication media in tourism promotion activities did not make tourism promotion run well. This was caused by, among others, the lack of funds to finance operations, problematic network systems, there were lack of IT and design expert permanent employees in the organisational structure, as well as inadequate office facilities and infrastructure.…”
Section: Regional Tourism Brandingsupporting
confidence: 86%
“…They were measuring the affective image in its sad-cheerful, and distressing-relaxing dimensions. For the significant variables, large effects were obtained, with the partial squared Eta (η 2 p) scores greater than 0.14 [87]. Data analysis reveals that cluster one (LO tourists) is the one that considers the island visited more pleasant and inspiring.…”
Section: Tourist Valuation Of Islands' Image and State Of Conservationmentioning
confidence: 95%
“…Web 2.0 offers a better communication experience from both sides (Eftekhari et al, 2010). So far, SM has become a valuable tool for destination marketing (Berhanu & Raj, 2020;Kanwel et al, 2019). The extensive range of SM platforms has made it challenging to reach the SM standard definition (Kaplan & Haenlein, 2010).…”
Section: Social Media In the Context Of Tourismmentioning
confidence: 99%